Phased grapevine genome sequence of an Rpv12 carrier for biotechnological exploration of resistance to Plasmopara viticola - Frommer, Bianca; Müllner, Sophia; Holtgräwe, Daniela; Viehöver, Prisca; Huettel, Bruno; Töpfer, Reinhard; Weisshaar, Bernd; Zyprian, Eva (Frontiers in Plant Science, 2023)
The downy mildew disease caused by the oomycete Plasmopara viticola is a serious threat for grapevine and can cause enormous yield losses in viticulture. The quantitative trait locus Rpv12, mediating resistance against P. viticola, was originally found in Asian Vitis amurensis. This locus and its genes were analyzed here in detail. A haplotype-separated genome sequence of the diploid Rpv12-carrier Gf.99-03 was created and annotated. The defense response against P. viticola was investigated in an infection time-course RNA-Seq experiment, revealing approximately 600 up-regulated Vitis genes during host-pathogen interaction. The Rpv12 regions of the resistance conferring and the sensitivity encoding Gf.99-03 haplotypes were structurally and functionally compared to each other. Two different clusters of resistance-related genes were identified within the Rpv12 locus. One cluster carries a set of four differentially expressed genes with three ACCELERATED CELL DEATH 6-like genes. The other cluster carries a set of six resistance gene analogues related to qualitative pathogen resistance. The Rpv12 locus and its candidate genes for P. viticola resistance provide a precious genetic resource for P. viticola resistance breeding. Newly developed co-segregating simple sequence repeat markers in close proximity to the R-genes enable its improved applicability in marker-assisted grapevine breeding.